The Spanish Civil War through the Female Gaze: A Valley of Betrayal (2007) by Tricia Goyer - Luna Carrasquer (Feminismo/s)
War literature is a highly gendered genre, having historically been almost exclusively associated with men. This resulted in the exclusion of women writers from the canon of war literature. However, particularly since the two World Wars, women have been increasingly participating in and writing about war. An example of this relates to the Spanish Civil War (1936-39), a conflict that still sparks the interest of both Spanish and international, and both male and female authors in the 21st century. Within this context, this paper analyses, from a gender perspective, Tricia Goyer’s Spanish Civil War novel A Valley of Betrayal (2007). It explores the representation of the war that this novel offers, as seen through the eyes of an American woman, and how this perspective establishes a dialogue with 20th-century male-authored canonical texts. Consequently, this paper analyses the way in which Goyer’s novel offers a female and foreign gaze on the conflict. Through the concepts of authorship, ‘authoritative witness’ (Schweik), transduction (Doležel), and exoticism, this paper illustrates that the novel offers an authorised, plastic-artistic, and exoticising gaze on the Spanish Civil War. It discusses how the novel’s main female character transforms into an authoritative witness by testifying to her wartime experiences through painting, and how Goyer interacts with the plastic-artistic and literary canon in order to give her representation of the Spanish Civil War. The relevance of this study is twofold: on the one hand, by discussing Goyer’s little-studied work, it aims to contribute to the scholarship on Spanish Civil War literature written by women; on the other, it seeks to examine what characterises the female gaze on the war in her novel. In this way, then, this paper explores one of the many ways in which women write about the Spanish Civil War, and the extent to which Goyer establishes a dialogue with the male-authored literary and plastic-artistic tradition.